Analysis of the Clinical and Radiological Results of Bridge Plate Versus External Fixation in Comminuted Distal Radius Fractures - Carula, Beatriz Canhoto (Thieme Revinter Publicações Ltda., 2021)

(untitled) (Rev Bras Ortop (Sao Paulo))
Objective  To evaluate and compare the clinical and radiological outcomes of patients with comminuted distal radius fractures treated with an external fixator or a dorsal bridge plate. Methods  In total, 45 patients were analyzed 1 year after surgery; 18 were treated with an external fixator, and 25 received a dorsal bridge plate. An analog pain scale and the Disabilities of the Arm, Shoulder and Hand (DASH) questionnaire were applied, in addition to radiographic, strength and range of motion assessments. Statistical analyzes were performed using the chi-squared test and the Mann-Whitney non-parametric test. Results  Fractures were more common in women over 60 years old who suffered falls from their own height. Both methods demonstrated similar functional and radiological results. Infections were more prevalent in patients receiving external fixators, but their residual grip strength was better. Reflex sympathetic neuropathy was more common in subjects treated with a dorsal bridge plate. Conclusion  Our analysis showed no consensus on the superiority of one method over the other. Each method had advantages and disadvantages, but both led to good, similar outcomes. The treatment must be chosen according to the profile of the trauma, the patient's clinical conditions, the surgeon's experience, and the availability of materials.